2008
DOI: 10.1167/iovs.07-1494
|View full text |Cite
|
Sign up to set email alerts
|

Using Human CD20-Transfected Murine Lymphomatous B Cells to Evaluate the Efficacy of Intravitreal and Intracerebral Rituximab Injections in Mice

Abstract: Inoculation of native or human CD20-transfected murine 38C13 cells in the vitreous or the brain of immunocompetent mice provides useful novel models for evaluating the biology and treatment of PIOL and PCNSL. Intravitreal and intracerebral rituximab injections reduced tumor occurrence and growth in each model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…For example, the murine 38C13 cell line expressing the human CD20 antigen has been used to evaluate the therapeutic potential of rituximab against intravenously injected disseminated tumors [43] and against central nervous system tumors [68]. The authors showed in the first case [43] that depletion of neutrophils, NK cells, and macrophages did not influence antibody efficacy, but complement inhibition abolished this effect.…”
Section: Models To Analyze the Efficacy Of New Therapiesmentioning
confidence: 99%
“…For example, the murine 38C13 cell line expressing the human CD20 antigen has been used to evaluate the therapeutic potential of rituximab against intravenously injected disseminated tumors [43] and against central nervous system tumors [68]. The authors showed in the first case [43] that depletion of neutrophils, NK cells, and macrophages did not influence antibody efficacy, but complement inhibition abolished this effect.…”
Section: Models To Analyze the Efficacy Of New Therapiesmentioning
confidence: 99%
“…Moreover, an efficient anti-tumor response can be induced in PCNSL but this has been very poorly investigated until now. It has nevertheless been shown in a murine model of nude mice that celecoxib was able to induce a prolonged survival time (Wang et al, 2006), or in a syngeneic murine model that rituximab was able to induce tumor rejection in some animals (Mineo et al, 2008). But no study assessed the anti-tumor immune response associated with tumor rejection.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Mineo et al [32] developed a murine model to evaluate the efficiency of intravitreal and intracerebral anti-CD20 monoclonal antibody (rituximab). In this model, human CD20-transfected murine B-lymphoma cells (38C13 CD20+) were inoculated in the vitreous cavity or in the brain caudate nucleus of immunocompetent syngeneic mice.…”
Section: B-cell Murine Models For Pvrlmentioning
confidence: 99%
“…The majority of early murine models for intraocular lymphoma that followed were predominantly of T-cell lineage [26,27,28,29]. To more closely simulate human intraocular lymphoma, B-cell murine models were eventually created [30,31,32,33]. As animal models for intraocular lymphoma continue to evolve, aspects such as the tissue distribution of lymphoma infiltration and whether or not the trafficking pattern of lymphoma cells closely mimics the human disease state have offered important practical considerations.…”
Section: Introductionmentioning
confidence: 99%